ERRORS AND CONSEQUENCES IN THE APPLICATION OF BOTULINUM TOXIN: A COMPREHENSIVE REVIEW (Editora Impacto Científico, 2025)
This article presents a comprehensive review of the errors and consequences associated with the application of botulinum toxin (BT) in aesthetic procedures. It analyzes the importance of facial anatomy, the mechanism of action of BT, the main errors in evaluation, dosage and technique, and the resulting complications, from mild reactions to serious complications. The aim is to provide valuable information for professionals and students, promoting safer and more effective practice. Complementary research included an analysis of recent studies on neurological complications and the importance of pharmacovigilance.